International Environmental Law and Climate Change Mitigation Efforts - Kemmala Dewi; Harmono Harmono; Sun Wei; Liu Yang; Benny Novico Zani (Yayasan Adra Karima Hubbi, 2025)
Background. Climate change is one of the most pressing global challenges, with significant consequences for ecosystems, economies, and human societies. International environmental law plays a critical role in shaping global efforts to mitigate climate change by establishing legal frameworks for cooperation and action. Objective. This study aims to analyze the role of international environmental law in climate change mitigation efforts, with a focus on the key legal instruments and agreements that shape global climate governance. The research seeks to evaluate the effectiveness of these legal frameworks in reducing greenhouse gas emissions and promoting sustainable environmental practices. Method. A qualitative research design was employed, using case studies, legal analysis, and interviews with environmental law experts, policymakers, and practitioners. The study examined major international agreements such as the Paris Agreement and the Kyoto Protocol to assess their impact on climate change mitigation efforts. Results. The findings indicate that while international environmental law has contributed to raising awareness and setting targets for climate change mitigation, the implementation of these efforts remains uneven, with many countries struggling to meet their commitments due to domestic challenges. Conclusion. The study concludes that international environmental law has been instrumental in global climate change efforts, but enhanced implementation mechanisms and greater international cooperation are necessary to achieve meaningful progress.